2023
DOI: 10.1021/acsptsci.2c00215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preclinical Evaluation of a Novel Fluorine-18-Labeled Tracer for Positron Emission Tomography Imaging of Bruton’s Tyrosine Kinase

Abstract: Bruton’s tyrosine kinase (BTK) is a target for treating B-cell malignancies and autoimmune diseases. To aid in the discovery and development of BTK inhibitors and improve clinical diagnoses, we have developed a positron emission tomography (PET) radiotracer based on a selective BTK inhibitor, remibrutinib. [18F]PTBTK3 is an aromatic, 18F-labeled tracer that was synthesized in 3 steps with a 14.8 ± 2.4% decay-corrected radiochemical yield and ≥99% radiochemical purity. The cellular uptake of [18F]PTBTK3 was blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…While the preliminary imaging studies herein did not show [ 11 C]evobrutinib to be a promising PET radiotracer for imaging the SARS‐CoV‐2 pseudovirus infection or LPS lung injury in mouse models, the development of BTK inhibitors for drug development and PET imaging remains an active area of interest. It is noteworthy that [ 18 F]BTK‐1 and [ 18 F]PTBTK 3 have recently been reported; however, both radiotracers revealed very high abdominal uptake in kidney, liver, and gastrointestinal organs in mice 38,39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the preliminary imaging studies herein did not show [ 11 C]evobrutinib to be a promising PET radiotracer for imaging the SARS‐CoV‐2 pseudovirus infection or LPS lung injury in mouse models, the development of BTK inhibitors for drug development and PET imaging remains an active area of interest. It is noteworthy that [ 18 F]BTK‐1 and [ 18 F]PTBTK 3 have recently been reported; however, both radiotracers revealed very high abdominal uptake in kidney, liver, and gastrointestinal organs in mice 38,39 …”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that [ 18 F]BTK-1 and [ 18 F]PTBTK 3 have recently been reported; however, both radiotracers revealed very high abdominal uptake in kidney, liver, and gastrointestinal organs in mice. 38,39 4 | CONCLUSIONS [ 11 C]Evobrutinib was successfully synthesized in comparative RCYs using a base-aided palladium-NiXantphos-mediated 11 C-carbonylation. Our ex vivo results were promising, with the visualization of tumors with [ 11 C]evobrutinib and its displacement in the presence of excess unlabeled evobrutinib.…”
Section: Dynamic Pet Imaging Of Mouse Models Of Lung Damagementioning
confidence: 99%
“…The method was slightly adapted from a previously published protocol. 53 The athymic nude mice were then subcutaneously injected with 4 × 10 6 U87MG cells (0.1 mL of 1:1 Matrigel/PBS) in the left flank. The mice were monitored closely until a palpable tumor was present.…”
Section: Boc-l-serine-tbu-233-d 3 (L-7)mentioning
confidence: 99%
“…Blocking studies demonstrated that [ 18 F]17 uptake in cells was consistent with a BTK-dependent mechanism. 22 Windhorst et al describe the synthesis and preclinical evaluation of [ 11 C]18 (Figure 2) as a PET tracer targeting both mutated epidermal growth factor receptor and anaplastic lymphoma kinase for non-small-cell lung cancer (NSCLC) imaging. 23 Another target for anticancer drug development is the C− X−C motif chemokine receptor 4 (CXCR4).…”
Section: Imaging and Therapymentioning
confidence: 99%
“…Tonge et al reported [ 18 F] 17 (Figure ) for PET imaging of BTK expression levels and target occupancy in vivo . Blocking studies demonstrated that [ 18 F] 17 uptake in cells was consistent with a BTK-dependent mechanism …”
Section: Radiopharmaceuticals For Cancer Imaging and Therapymentioning
confidence: 99%